Strategi Pemasaran Tepat Sasaran: Suatu Upaya Peningkatan Jumlah Anggota BMT (Studi Kasus Di Kabupaten Nganjuk) - Solihin Solihin (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2018)
The rapid economic activity of sharia-based societies makes the presence of independent regulation a necessity. Sharia banks and BPRS are subject to Bank Indonesia regulations. Whereas Microfinance Institutions (MFIs) in the form of BMTs until now there are no independent regulations and the reality is legal entity cooperatives that are subject to cooperative regulations (Law No. 17 of 2012) and specifically regulated in the Decree of the Minister of Cooperatives and UKMRI No. 91 / Kep / M / KUKM / IX / 2004. BMT in Nganjuk Regency in an effort to increase the number of its members to implement the right Targeted Financing Product Marketing Strategy means that the products offered by BMT in the form of fund raising and financing are products that are really in demand by members and prospective members (on request) so that in turn increase the number of members. Because BMT is a sharia-based MFI that is inseparable from the supervision of a Sharia Supervisory Bank that must comply with and comply with the regulations issued by the MUI's Fatwa Supervisory Board.